1999
DOI: 10.1042/cs19990137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidosis on leptin secretion from 3T3-L1 adipocytes and on serum leptin in the uraemic rat

Abstract: Marked hyperleptinaemia and metabolic acidosis are common findings in patients with chronic renal failure. In animal models, both leptin administration and acidosis reduce food intake. However, leptin causes loss of body fat, while acidosis induces muscle wasting. Whether a low pH and leptin production are related has not been studied. Leptin secretion was measured in cultured 3T3-L1 adipocytes exposed to acid or control pH for up to 96 h. In addition, serum leptin was compared between acidotic and bicarbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…Metabolic acidosis has been shown to decrease serum leptin in uremic rats through suppression of leptin secretion from adipocytes [27], in agreement with our finding. In contrast, other previous studies reported that blood hydrogen ion concentration does not influence substantially or only moderately leptin serum concentrations, or the correction of metabolic acidosis in dialysis patients can decrease leptin [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Metabolic acidosis has been shown to decrease serum leptin in uremic rats through suppression of leptin secretion from adipocytes [27], in agreement with our finding. In contrast, other previous studies reported that blood hydrogen ion concentration does not influence substantially or only moderately leptin serum concentrations, or the correction of metabolic acidosis in dialysis patients can decrease leptin [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…A low pH of 7.1 was associated with a significantly reduced leptin output both at 48 and 96 h, confirming our previous report (9) (Figure 1). In contrast, leptin mRNA was not affected by low pH at 48 h ( Figure 2).…”
Section: Effect Of Acidosis On Leptin Secretion and Leptin Gene Expresupporting
confidence: 82%
“…In contrast, circulating leptin acutely decreases after fasting or calorie restriction in both rodents and humans (7,8). Like starvation, metabolic acidosis is associated with lower serum leptin in uremic rats (9). However, the mechanism or mechanisms that link acidosis and leptin is unknown.…”
mentioning
confidence: 98%
See 2 more Smart Citations